Androgen Insensitivity Syndrome (AIS): A Case History (Ibrahim Cardiac Medical Journal, 2015)
Androgen Insensitivity Syndrome (AIS) is an inherited X-linked recessive disease with a mutation in the Androgen Receptor (AR) gene resulting in - functioning of Y sex chromosome and abnormality on X sex chromosome, where affected individuals have male chromosomes and male gonads with complete or partial feminization of the external genitals. Recently a case of complete Androgen Insensitivity Syndrome (CAIS) is reported at Shaheed Suhrawardy Medical College, Dhaka. A 15 years old school girl was admitted with primary amenorrhea with bilateral inguinal hernia. Diagnosis of complete AIS is confirmed by discovering an adult male testosterone level, 46, XY karyotype, absence of axillary and pubic hair and a shallow vagina, with no cervix or uterus.Ibrahim Cardiac Med J 2014; 4(1): 33-37